2018
DOI: 10.1111/pedi.12793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of continuous glucose monitoring system for detection of alterations in glucose homeostasis in pediatric patients with β-thalassemia major

Abstract: Background Disturbances of glucose metabolism are common in β‐thalassemia major (β‐TM). Aim This study was conducted to assess the pattern of glucose homeostasis in pediatric β‐TM patients comparing oral glucose tolerance test (OGTT) and continuous glucose monitoring system (CGMS). Methods Two‐hundred β‐TM patients were studied and those with random blood glucose (RBG) ≥7.8 mmol/L (140 mg/dL) were subjected to OGTT, insertion of CGMS and measurement of fasting C peptide, fasting insulin, and hemoglobin A1c (Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Our study had two main limitations. The first was the use of FBS instead of methods with higher diagnostic capabilities including continuous monitoring of serum glucose and oral glucose tolerance test (OGTT) for the detection of glycemic abnormalities [39]. However, these methods are time-consuming and cause some inconvenience to the patients and we failed to use them.…”
Section: Discussionmentioning
confidence: 99%
“…Our study had two main limitations. The first was the use of FBS instead of methods with higher diagnostic capabilities including continuous monitoring of serum glucose and oral glucose tolerance test (OGTT) for the detection of glycemic abnormalities [39]. However, these methods are time-consuming and cause some inconvenience to the patients and we failed to use them.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endocrine complications, due to iron overload, account for significant morbidity, such as diabetes mellitus (DM). 1,2 Hemoglobin A1c (HbA1C), which is important for evaluating glucose metabolism, can reflect the average blood glucose status from the previous 2-3 months. However, HbA1c is susceptible to other factors, such as erythropoiesis, hemoglobin disease, glycosylation levels, and erythrocyte longevity.…”
Section: Introductionmentioning
confidence: 99%
“…El-Samahy et al studied 20 beta thalassaemia patients with random blood glucose >7.8 mmol, who then had OGTT and CGMS. OGTT detected 6/20 patients (30%) who had impaired glucose tolerance and 7/20 (35%) patients who were in the diabetic range, while CGMS found that 7/20 (35%) patients had IGT and 13/20 (65%) had frank diabetes mellitus [64].…”
Section: Glucose Intolerance and Diabetes Mellitusmentioning
confidence: 98%
“…Kanbour et al found that patients with very high liver iron concentration (LIC) (>30 mg Fe/gm dry liver) were more likely to have a higher prevalence of impaired fasting glucose when compared to those with lower LIC (p = 0.044) [55]. The use of continuous glucose monitoring (CGMS) in detecting glucose intolerance and diabetes mellitus has also been studied, with CGMS found to be superior when compared to OGTT (p = 0.012) [64]. El-Samahy et al studied 20 beta thalassaemia patients with random blood glucose >7.8 mmol, who then had OGTT and CGMS.…”
Section: Glucose Intolerance and Diabetes Mellitusmentioning
confidence: 99%